Biomechanical Comparison of an All-Soft Suture Anchor With a Modified Broström-Gould Suture Repair for Lateral Ligament Reconstruction. (February 2014) - Brown, Christopher A.; Hurwit, Daniel; Behn, Anthony; Hunt, Kenneth J.
Background: Anatomic repair is indicated for patients who have recurrent lateral ankle instability despite nonoperative measures. Hypothesis: There is no difference in repair stiffness, failure torque, or failure angle between specimens repaired with all-soft suture anchors versus the modified Broström-Gould technique with sutures only. Study Design: Controlled laboratory study. Methods: In 10 matched pairs of human cadaveric ankles, the anterior talofibular ligament (ATFL) was incised from its origin on the fibula. After randomization, 1 ankle was repaired to its anatomic insertion using two 1.4-mm JuggerKnot all-soft suture anchors; the other ankle was repaired with a modified Broström-Gould technique using 2-0 FiberWire. All were augmented using the inferior extensor retinaculum. All ankles were mounted to the testing machine in 20° of plantar flexion and 15° of internal rotation and loaded to failure after the repair. Stiffness, failure torque, and failure angle were recorded and compared using a paired Student t test with a significance level set at P < .05. Results: There was no significant difference in failure torque, failure angle, or stiffness. No anchors pulled out of bone. The primary mode of failure was pulling through the ATFL tissue. Conclusion: There was no statistical difference in strength or stiffness between a 1.4-mm all-soft suture anchor and a modified Broström-Gould repair with 2-0 FiberWire. The primary mode of failure was at the tissue level rather than knot failure or anchor pullout. Clinical Relevance: The particular implant choice (suture only, tunnel, anchor) in repairing the lateral ligament complex may not be as important as the time to biological healing. The suture-only construct as described in the Broström-Gould repair was as strong as all-soft suture anchors, and the majority of the ankles failed at the tissue level. For those surgeons whose preference is to use anchor repair, this novel all-soft suture anchor may be an alternative to other larger anchors, as none failed by pullout.